Knowledge management system model in enhancing knowledge facilitation of software process improvement for software house organization. - Abdullah, Rusli; Mohamed Talib, Amir (2012)
Software Process Improvement (SPI) is necessity to any Software House Organization (SHO). Process improvement requires embedding the knowledge into SHO's practice and structure especially in promoting and facilitating knowledge of best practice in SPI for the benefits of members of community of practice (CoP). Hence, in this paper, knowledge management (KM) and knowledge facilitation are investigated in order to find practical means to reach process improvement regarding with software development environment. In particular this study, it is also concerned with the process of Knowledge Management System (KMS) in supporting the knowledge facilitation of SPI for SHO. In order to understand the support process, we have studied how KM processes are practiced within SHO which includes communication, learning, sharing and documentation process. The findings explain on how the KMS has been practiced and influence the SPI in SHO. This result indicates that KM processes in SHO are being undertaken in a very informal manner, which has caused SHO to be more informal in their KM processes specifically and SPI generally.